2016
DOI: 10.1159/000447247
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Patients with Chronic Thromboembolic Disease

Abstract: Background: Patients with chronic thromboembolic pulmonary disease (CTED) have persistent pulmonary vascular obstruction and exercise intolerance without pulmonary hypertension at rest and may benefit from pulmonary endarterectomy. However, up to now, CTED has been poorly characterized. Objectives: This study aimed to analyze the exercise capacity and limiting factors in CTED. Methods: We compared right heart catheterization and cardiopulmonary exercise test results of patients with CTED [mean pulmonary artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 23 publications
5
71
0
9
Order By: Relevance
“…Assuming that persisting or progressive functional and/or hemodynamic impairment after acute PE is an early indicator of the subsequent development of CTEPH, PPEI has been defined as a coprimary outcome in the FOCUS study . Indeed, a recent cohort study demonstrated that patients fulfilling all diagnostic criteria of CTEPH despite elevation of mean pulmonary artery pressure (a condition called “chronic thromboembolic disease”) showed similar objective functional impairment using cardiopulmonary exercise testing compared to patients with CTEPH . These assumptions become of clinical importance if aiming to define who, when, and how patients should be followed after acute PE.…”
Section: Discussionmentioning
confidence: 53%
“…Assuming that persisting or progressive functional and/or hemodynamic impairment after acute PE is an early indicator of the subsequent development of CTEPH, PPEI has been defined as a coprimary outcome in the FOCUS study . Indeed, a recent cohort study demonstrated that patients fulfilling all diagnostic criteria of CTEPH despite elevation of mean pulmonary artery pressure (a condition called “chronic thromboembolic disease”) showed similar objective functional impairment using cardiopulmonary exercise testing compared to patients with CTEPH . These assumptions become of clinical importance if aiming to define who, when, and how patients should be followed after acute PE.…”
Section: Discussionmentioning
confidence: 53%
“…CTED patients show the same exercise limitations and symptoms as World Health Organization (WHO) Functional Class II or III CTEPH patients as described by DONAHOE et al [7]. These symptoms are in line with an inadequate response in pulmonary haemodynamics during exercise [8][9][10]. Successful PEA has been reported in a limited number of patients with CTED without mortality [9,10].…”
Section: Introductionmentioning
confidence: 78%
“…To further complicate the issue, the term “chronic thromboembolic disease” is increasingly used in the medical literature in recent years. While most experts agree that chronic thromboembolic disease is defined as persistent pulmonary vascular occlusion in the absence of pulmonary hypertension, it remains controversial whether actual documented impaired physical performance should also be part of chronic thromboembolic disease 25, 26. It might be interesting to hypothesize that post‐PE syndrome includes a spectrum of post‐PE patients: from those with symptoms and exercise intolerance with no or mild residual imaging abnormalities (as described in this paper), to those with symptoms, residual vascular obstruction, but minimal hemodynamic abnormalities (chronic thromboembolic disease), to full‐blown chronic thromboembolic pulmonary hypertension with symptoms, residual vascular obstruction and pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%